Design of Child Friendly School Through Assistance in Preparing Differentiated Teaching Modules for PAUD Teachers in Banda District: Desain Sekolah Ramah Anak Melalui Pendampingan Penyusunan Modul Ajar Berdiferensiasi Bagi Guru PAUD di Kecamatan Banda - Nursalam; Amir, Israwati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
The purpose of this community service is to support the enhancement of understanding among early childhood education (PAUD) teachers in Banda District in developing differentiated teaching modules as a principle of Child-Friendly Schools (SRA). This community service was carried out using the Participatory Action Research (PAR) method. The results of this service identified the main obstacles in developing differentiated teaching modules, which were caused by the teachers' limited initial understanding of the concept of differentiated teaching modules and the teachers' educational background, which was not relevant to the PAUD level. Additionally, the outcome of this assistance successfully provided the necessary knowledge to the PAUD teachers and improved their capacity to develop teaching modules that align with the children's needs and the SRA principles.